1977
DOI: 10.2466/pr0.1977.40.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Measures of Locus of Control for Black and White Students

Abstract: Past research has involved various measures of locus of control. In the present study, Rotter's Internal-External (I-E) Scale, Levenson's Internal, Power, and Chance scales and some items from Coleman's study of equality of educational opportunity were administered to northern white and southern black college students. In general, the relationships between the measures did not vary by race or sex. Multiple regression analyses showed that Rotter's I-E Scale was significantly related to Levenson's Chance and Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…A similar pattern (.24, .44, -.15) has been found by Donovan and O'Leary (1978) in an alcoholic sample and by Hall, Joesting, and Woods (1977) in a group of northern white and southern black college students (.22, .43, -.32). Furthermore, Hall et al (1977) computed a step-wise multiple regression analysis in an effort to predict the Rotter I-E Scale scores from the multidimensional I, P, and C Scales. Furthermore, Hall et al (1977) computed a step-wise multiple regression analysis in an effort to predict the Rotter I-E Scale scores from the multidimensional I, P, and C Scales.…”
Section: Relationship To Rotter's Scalesupporting
confidence: 77%
See 1 more Smart Citation
“…A similar pattern (.24, .44, -.15) has been found by Donovan and O'Leary (1978) in an alcoholic sample and by Hall, Joesting, and Woods (1977) in a group of northern white and southern black college students (.22, .43, -.32). Furthermore, Hall et al (1977) computed a step-wise multiple regression analysis in an effort to predict the Rotter I-E Scale scores from the multidimensional I, P, and C Scales. Furthermore, Hall et al (1977) computed a step-wise multiple regression analysis in an effort to predict the Rotter I-E Scale scores from the multidimensional I, P, and C Scales.…”
Section: Relationship To Rotter's Scalesupporting
confidence: 77%
“…There were no differences on the I or C Scales. In a number of other studies (e.g., Hall, Joesting & Woods, 1977;Krampen & Nispel, 1978;Zukotynski & Levenson, 1976) no significant gender differences were found but Mahler (1974) discovered that Japanese females scored significantly higher than Japanese males on the perception that their lives were controlled by powerful other people. In a number of other studies (e.g., Hall, Joesting & Woods, 1977;Krampen & Nispel, 1978;Zukotynski & Levenson, 1976) no significant gender differences were found but Mahler (1974) discovered that Japanese females scored significantly higher than Japanese males on the perception that their lives were controlled by powerful other people.…”
Section: Influence Of Demographic Factorsmentioning
confidence: 95%
“…A strong relationship was found to exist between race and locus of control orientation. As suggested by previous research (Battle & Rotter, 1963;Hall et al, 1977;Lefton, 1968) the white subjects in this study were more internal in their locus of control than the non-white subjects.…”
supporting
confidence: 65%
“…He also found that among the high pay group the black workers were more external and had higher anomie scores than the white workers. Hall, Joesting, and Woods (1977) studied students from predominantly black and white universities and found evidence to suggest that there existed a sense of powerlessness against a hostile environment among the black and female subjects.…”
Section: Specific Researchmentioning
confidence: 99%
“…Factor analysis confirmed three scales in two studies (Levenson, 1973, 1974). Convergent evidence for validity included significant correlations, in the expected directions, of the I, P, and C subscales with Rotter's (1966) Internal–External Locus of Control Scale (Donovan & O'Leary, 1978; Hall, Joesting, & Woods, 1977).…”
Section: Methodsmentioning
confidence: 93%